INTEGRATING NEUROSCIENCE AND ISLAMIC EDUCATION TO PROMOTE CHILD-FRIENDLY SCHOOLS: A CASE STUDY OF ELEMENTARY SCHOOLS IN YOGYAKARTA CITY - Widodo, Hendro; Jailani, Mohammad; Hidayat, Panji (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
This research focuses on presenting a model for developing Child-Friendly Schools (SRA) in Yogyakarta's primary schools by combining principles from neuroscience and Islamic education. Employing a qualitative descriptive approach, the study engages school principals, teachers, and students as research subjects. Data collection entails observations, interviews, and documentation, with data validity ensured through source and technique triangulation. Analysis follows Miles Huberman's Interactive Model, encompassing data reduction, presentation, and conclusion/verification. The study reveals that SD Negeri Giwangan and SD Negeri Ngupasan effectively implement child-friendly school practices according to Yogyakarta Mayor's Decree No. 434 of 2016. These schools prioritize six essential indicators: 1) SRA Policy, 2) Curriculum implementation, 3) Training of educators and staff in children's rights, 4) SRA facilities and infrastructure, 5) Fostering child participation, and 6) Encouraging parent involvement. The incorporation of neuroscience insights and Islamic education principles has notable positive implications. This approach contributes to shaping students' behavior to become both well-behaved and child-friendly. Moreover, it facilitates the creation of an enjoyable learning environment and nurtures students' imaginative capabilities. Abstrak: Penelitian ini bertujuan mendeskripsikan model pengembangan Sekolah Ramah Anak (SRA) berbasis neurosains dan pendidikan Islam di SD Kota Yogyakarta. Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek Penelitian adalah kepala sekolah, guru, dan siswa. Teknik Pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Keabsahan data menggunakan Triangulasi sumber dan teknik. Analisis Data menggunakan Model Interaktif Miles Huberman mencakup reduksi data, penyajian data, penarikan kesimpulan/verifikasi. Hasil penelitian ini adalah SD Negeri Giwangan dan SD Negeri Ngupasan menerapkan sekolah ramah anak berdasarkan Surat Keputusan Walikota Yogyakarta Nomor 434 Tahun 2016. Kedua sekolah tersebut menerapkan 6 (enam) indikator Sekolah ramah anak yaitu 1) Kebijakan SRA, 2). Pelaksanaan kurikulum, 3). Pendidik dan tenaga kependidikan terlatih hak-hak anak, 4). Sarana dan prasarana SRA, 5). Partisipasi anak, dan 6). Partisipasi orang tua. Implikasi dari neurosains dan pendidikan Islam membantu peran siswa berlaku baik dan ramah anak. Menciptakan suasana lingkungan sekolah yang menyenangkan dan menumbuhkan sikap imajinasi kreatif siswa.